Work-life balance policies in Malaysia: theory and practice - Noor, Noraini M.; Mohd Mahudin, Nor Diana (Edward Edgar Publishing, 2015)
In this chapter we examine work-life balance policies and initiatives in Malaysia. We begin by first considering the Employment Act (1955), the most important legislation that specifies the minimum working terms related to wages, working hours, leave, termination and lay-off benefits for employees in the country. Next, we discuss women’s employment and in the process of strengthening human resources, the work-life policies and practices that have been initiated to help them harmonize between their work and family. In reality, however, these work-life balance practices are sorely lacking, especially for those who most needed them. We present data based on an exploratory study examining the availability and use of some of these work-life balance initiatives within a university setting in the country and discuss their implications on employees. Finally, taking into account current realities and employees’ needs for better work-life balance, we conclude with several suggestions. These include addressing cultural norms regarding gender roles; direct intervention by the state to change how work and family are perceived, and to transfer care from the home to the public sector; and mandating public and private sectors to provide work-life policies within their organizations.